The influence of job satisfaction and leadership style on organisational commitment in the BRIMOB Unit of the Jambi Regional Police - Ronal Regen; Furqon Benny Atmaja; Andre Ramadani; Eva Saputra; Helvi Lusiana (Jurnal Mantik, 2023)
This study aims to analyze the effect of job satisfaction and leadership style on organizational commitment in the Jambi Regional Police Brimob Unit. Job satisfaction and leadership style are known as key factors that influence an individual's level of commitment to the organization where they work. The research method used is quantitative with a descriptive approach. Data were collected through questionnaires and analyzed using Multiple Linear Regression Analysis with 45 respondents. The results showed that job satisfaction has a significant effect on organizational commitment in the Jambi Police Brimob Unit. The more satisfied members are with their jobs, the higher their level of commitment to the organization. In addition, leadership style also has a positive and significant effect on organizational commitment. These results provide important insights into the factors that influence organizational commitment in the work environment. This study has important practical implications. Management can use the results of this study to develop strategies that increase job satisfaction and the effectiveness of leadership styles in the Brimob Unit. Members who are committed to the organization tend to be more productive and contribute positively to the success of the agency. Therefore, understanding and managing these factors can contribute to the achievement of organizational goals. Thus, this study highlights the importance of human resource development, leader training, and effective human resource management in supporting stronger organizational commitment in the work environment of the Brimob Unit.